Legal Impact of Exoneration Clauses in Standard Contract Deeds with High Legal Risk - Nur Fitria Dewi, Feni; Hasana, Dahniarti (TABELLIUS: Journal of Law, 2025)
This study aims to analyze: 1) The position of the exoneration clause in a standard agreement deed according to the provisions of positive law in Indonesia. 2) The legal impacts arising on the parties of the exoneration clause included in a standard agreement deed that contains high legal risks. This type of research is normative legal research. The approach method in this study is the statute approach. The type of data in this study is secondary data. The data collection method uses library techniques (study document). The analysis in this study is prescriptive. The results of the study concluded: 1) The position of the exoneration clause in a standard agreement deed according to the provisions of positive law in Indonesia is legally very limited because it has the potential to eliminate the responsibility of business actors and create an imbalance in bargaining positions in contractual relationships. Although the principle of freedom of contract is recognized in Article 1338 of the Civil Code, the exoneration clause cannot be enforced if it is contrary to the law, public order, morality, and the principle of good faith. This provision is reinforced by sectoral regulations such as POJK 1/POJK.07/2013, air transportation regulations, and various other provisions that emphasize that business actors' responsibilities cannot be transferred through agreements. Jurisprudence such as the Bandung High Court Decision Number 459/PDT/2018/PT.BDG and the Supreme Court Decision Number 1391 K/Pdt/2011 also demonstrate the courts' consistency in rejecting the validity of exoneration clauses that are drafted unilaterally and are detrimental to the weaker party. 2) The legal impact that arises for the parties if the exoneration clause is included in a standard agreement deed that contains high legal risks is that the clause has broad legal consequences because it contradicts the principles of justice, propriety, and the provisions of Article 1337 of the Civil Code and Article 18 of the Consumer Protection Law. In civil law, this clause is generally declared invalid and non-binding. Administratively, business actors can be subject to sanctions by sector regulators such as the Financial Services Authority (OJK), the Ministry of Transportation, or insurance authorities. Notaries who leave such clauses in deeds also risk facing administrative liability.